A Study of Life Satisfaction among Elderly: A Comparison between those Practicing Yoga and those Not Practicing Yoga - Paliwal , Suprithy (International Journal of Psychosocial Rehabilitation, 2020)
The objective of the study was to assess the difference in life satisfaction between those elderly who practiced yoga and those who did not practice yoga. A purposive random sampling technique was used, and a sample of 200 elderly people above the age of 60 years was included in the study. Out of the sample, 100 were those who were practicing yoga at a yoga center daily, and the remaining 100 were not practicing yoga. Out of the 100 in each group, 50 were males and the remaining 50 were females. Life satisfaction was measured using the Life Satisfaction Scale standardized by Proma Singh and George Joseph. To analyze the results, the statistical methods that were used were mean, standard deviation, and “t” test. Results indicate that there is a significant difference in life satisfaction (t-value = 15.29, significant at the .01 level) among the elderly who practice yoga and those who do not practice yoga. The mean scores of 154.29 and 122.83 are also indicative that the elderly people who practice yoga are more satisfied compared to those who do not practice yoga. The study also shows a significant difference in life satisfaction among males and females of the group practicing yoga (t-value of 2.72, significant at the .01 level). The results indicate that females (157.34) are higher on life satisfaction compared to males, whose mean scores are (151.24). No significant difference (t-value of .39) was found between males and females of the group not practicing yoga. The mean scores of 122.92 for males and 122.74 for females are also indicative of the same.